Connecting the actors, discovering the ties : exploring disaster risk governance network in Asia and the Pacific - Trias, Angelo Paolo Luna (2020)
Disaster risk reduction (DRR) arrangement can be seen as an ecosystem that has been jointly governed by stakeholders ranging from governments, non-governmental organizations, civil society and faith-based groups, scientific bodies, research institutes and universities, the private sector and local communities. This paper investigates DRR ecosystem in the Asia Pacific region by systematically analysing the network of DRR projects in the Asia-Pacific between 2000 and 2012 as listed in the DRR projects database (www.drrproject.net). The projects generally aiming at shaping discourse, policy and practice around various priorities of disaster risk reduction at different levels. The research explores network structures by analysing organizational connections using network theory and/or social network analysis (SNA) techniques. It examines how DRR organizational networks function and behave by exploring the connections and interactions (i) between donors, the projects they support, and the countries (recipient government) they aid and assist, as well as those (ii) between donors, the lead organizations managing the projects, and their implementing partner organizations. The research seeks to contribute to further understand disaster risk governance as a network and an ecosystem.